Entrepreneurial Knowledge on Entrepreneurial Intention: The Mediating of Perceived Desirability and Perceived Feasibility - Yekti Sulistyorini; Budi Santoso (BASKARA : Journal of Business and Entrepreneurship, 2021)
Entrepreneurship plays an important role in the creation and growth of business as well as the growth and prosperity of the region and the country. The importance of entrepreneurship in job creation and economic development is recognized worldwide. This  research  is  motivated  by  the  low  entrepreneurial  intention  of  Vocational  High  School students which is also have an impact on unemployment. This study aims to determine and analyse the mediating effect of perceived desirability and perceived feasibility on the effect of entrepreneurial knowledge on entrepreneurial intention. The method used in study is an explanatory survey research with data collection techniques through a questionnaire and observation. The population of this study were students of PGRI Bandung Vocational High School class XI and XII academic year 2019/2020 as many as 305 students and sample of this research is 176 students. The results show that: 1) entrepreneurial knowledge has a significant effect on entrepreneurial Intention 2) perceived desirability mediates the effect of entrepreneurial knowledge on entrepreneurial intention 3) perceived feasibility mediates the effect of entrepreneurial knowledge on entrepreneurial intention.